Blended diets for gastrostomy fed children and young people: a scoping review. Issue 5 (15th May 2018) - Breaks, Anne; Smith, Christina; Bloch, Steven; Morgan, Sally
Abstract: Background: The present review aimed to identify what is known about the use of blended diets in gastrostomy fed children and young people (i.e. children and young people refers to those who are aged up to 25 years with special educational needs or a disability in accordance with Part 3 of the Children and Family Act 2014; within the review, the word children is used for simplicity but encompasses young people too) and to identify gaps in the literature on this topic to inform future research and policy. Methods: A scoping review methodology was used searching the online databases PUBMED, PsychINFO, CINAHL, SCOPUS and AMED, EMBASE for articles that addressed issues pertaining to blended diets. The review identified a broad range of literature, regardless of study design, and described and evaluated the quality, range and nature of research activity related to the use of blenderised diets. Results: Forty‐three studies were included in the review. The studies focused on nutrition, equipment, the views of carers and patients, and the views of professionals. Several studies described the lack of evidence regarding pros and cons of blended diets and highlighted the need for further research into the field. Conclusions: There were gaps in the evidence base regarding the impact of blended diets on the health and well‐being of the children who receive them and upon the carers who feed the children. The nutritional impact of blended diets is not fully understood and the knowledge and views of professionals involved in the care of those receiving blended diets varies.